Proceedings of the 3rd Asian Education Symposium (AES 2018) 2019
DOI: 10.2991/aes-18.2019.37
|View full text |Cite
|
Sign up to set email alerts
|

Development of Low-Cost Spectrophotometry Laboratory Practice Based on the Digital Image for Analytical Chemistry Subject

Abstract: A module for laboratory practice in quantitative analytical chemistry subject has been developed. The method uses digital image colorimetry as a basis for low-cost spectrophotometry analysis. Reduction-oxidation reaction of silver nanoparticle and mercury (II) ion was used as a case study for the colorimetric experiment. The yellow color of silver nanoparticle was faded linearly to colorless with the addition of mercury ion as an analyte. The color change was then recorded with a digital camera and processed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…While a number of different algorisms exist, the RGB (red, green, and blue) color space is the most popular approach to describe a color quantitatively [29,31,32]. As presented in the Supplementary Materials (Figure S2), we have shown that the normalized R value (R/RGB) is the best choice for analyzing the colorimetric assay for anthocyanins on the PDMS chip.…”
Section: Chip Design and Mobile Colorimetric Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…While a number of different algorisms exist, the RGB (red, green, and blue) color space is the most popular approach to describe a color quantitatively [29,31,32]. As presented in the Supplementary Materials (Figure S2), we have shown that the normalized R value (R/RGB) is the best choice for analyzing the colorimetric assay for anthocyanins on the PDMS chip.…”
Section: Chip Design and Mobile Colorimetric Analysismentioning
confidence: 97%
“…Digital image analysis has been extensively used for quantifying colorimetric assays, which is typically performed by using a smartphone, digital camera, or scanner to capture the image and process the color information [31]. As such, all mini-vails on the microchip were essentially adapted for performing the colorimetric assays; as shown in Figure 4, the two rows of assay vials with different concentrations of Cy3G showed varied colors, from plain gray to bright pink in the top row (pH 1.0), with essentially no clear color change in the bottom row (pH 4.5).…”
Section: Chip Design and Mobile Colorimetric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…laboratory experiments are important to achieve learning objectives and to enrich students' Cognitive, Affective and psychomotor abilities. Through this practical learning activity, the concepts and theories learned in the classroom will be observed and verified by students using real experiments (Firdaus et al, 2019). Learning facilities are one of the factors supporting the success of learning activities (Bima et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Another example represents a devices that monitors the wavelength-ratiometric resonance Rayleigh scattering signal of the chemical sensor upon white-LED illumination [32]. Other groups developed modules that are based on digital image colorimetry (via smartphone) [33] or make use of a diffraction grating and image processing to measure the particle size and concentration [34], or use a tungsten-filament lamp with optical fibers and a commercial portable spectrometer [35].…”
Section: Introductionmentioning
confidence: 99%